The spillover of shadow interest rate to the excess returns in emerging markets - Oguzhan Ozcelebi; Mehmet Tevfik Izgi (Economic Journal of Emerging Markets, 2021)
Purpose - This study focuses on the monetary policy transmission of the U.S. on the excess returns in emerging markets by estimating the impacts of changes in the shadow interest rate in the U.S. on the Barclays Benchmark EM FX Trend Excess Return Index (FXERI) and the Barclays Cross Asset Trend Index – EM FX ER (CRASERI).